KONFLIK TANAH PERKEBUNAN ANTARA MASYARAKAT DENGAN PT DI KENAGARIAN AUA KUNING KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Meldawati mel (Laboratorium Program Studi Pendidikan Sejarah Sekolah Tinggi Keguruan dan Ilmu Pendidikan, 2018)
Land conflicts in West Sumatra, in general are ulayat land conflicts, both between indigenous peoples (internal-horizontal conflicts) and between indigenous peoples and third parties (internal-vertical conflicts), especially with government, private, legaland military corporations. West Pasaman Regency is one of the regencies that has fertile land, many people depend on oil palm agriculture. One of them is Pasaga Kenagarian Subdistrict Aua Kuniang, is one of the sub-districts located in West Pasaman Regency which has the potential of abundant and abundant natural wealth. Therefore the community of Kenagarian Aua Kuniang is almost 70 percent dominant as oil palm farmers. The emergence of oil palm companies that are highly related to land, it is not uncommon to find land conflicts, especially land conflicts between companies themselves and local communities. This problem is how the background of the plantation land conflict between the community and PT. in Kenagarian Aua Kuniang, as for the purpose of this paper the purpose of this study is to describe the background of the occurrence of plantation land conflicts between the community and PT. in Kenagarian Aua Kuniang. This method of writing uses historical methods that go through four stages, namely heuristics, source criticism, synthesis and interpretation and historiography.